Constructal theory of distribution of city sizes. - Bejan, A.; Lorente, S.; Miguel, A. F.; Reis, A (John Wiley & Sons, 2006)
Every sector of society is a conglomerate of mating flows that morph in time in order to flow more easily: people, goods, money, information, and so on. Like all the flows of nature and engineering, social constructs are "alive". The view that society is a flow system with intertwined morphing (improving) architectures was part of the original disclosure of constructal theory.
Keywords: city size; constructal law